2005
DOI: 10.1158/1078-0432.ccr-04-2623
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Adverse Effects in Cynomolgus Macaques Treated with CNTO 95, a Fully Human Anti-αv Integrin Monoclonal Antibody, Despite Widespread Tissue Binding

Abstract: Purpose: CNTO 95 is a fully human anti-av integrin monoclonal antibody that inhibits macaque and rodent angiogenesis and inhibits human tumor growth in rodents. The purpose of these studies was to evaluate the preclinical safety of long-term administration of CNTO 95 in cynomolgus macaques. Experimental Design: The in vitro binding profiles of CNTO 95 to human and macaque tissues and the in vivo binding to macaque tissues was evaluated by immunohistochemistry. The preclinical safety of CNTO 95 (10 and 50 mg/kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 23 publications
2
36
0
Order By: Relevance
“…Also, perfluorocarbon-lecithin emulsions have already been approved for clinical use as blood substitutes (Perflubron). Furthermore, integrin antibodies and peptibodies have proved safe in phase 1 and 2 clinical trials (52)(53)(54)(55)(56)(57). Thus, we do not anticipate toxicities from these 2 components of the nanoparticulate system.…”
Section: Discussionmentioning
confidence: 95%
“…Also, perfluorocarbon-lecithin emulsions have already been approved for clinical use as blood substitutes (Perflubron). Furthermore, integrin antibodies and peptibodies have proved safe in phase 1 and 2 clinical trials (52)(53)(54)(55)(56)(57). Thus, we do not anticipate toxicities from these 2 components of the nanoparticulate system.…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, caution should be used in extrapolating these safety and toxicity data from rats to human patients. However, data from a preclinical toxicity study in cynomolgus macaques showed that treatment with intetumumab produced no sign of toxicity and no histopathologic changes in any of the tissues examined (2). Data from two recently completed phase I clinical trials (6, 7) further showed that intetumumab was generally safe and well tolerated either alone or in combination with docetaxel in 6-week or prolonged treatment regimens.…”
Section: Discussionmentioning
confidence: 99%
“…1). Preclinical studies have shown that intetumumab exhibits antiangiogenic and antitumor activity in human cancer xenograft models in nude mice (1)(2)(3). Intetumumab has been reported to inhibit cell adhesion, migration, invasion, and proliferation of endothelial cells and tumor cells in vitro and tumor metastasis in vivo in nude mice with human breast cancer xenografts by inactivating the focal adhesion kinase (FAK) and the docking protein paxillin (1,4).…”
Section: Introductionmentioning
confidence: 99%
“…4). Preclinical studies have shown that CNTO 95 exhibits antitumor and antiangiogenic activity in human cancer xenograft models when used as a single agent with few adverse effects (4,5). Recently, a phase I study of CNTO 95 in patients with advanced solid tumors has shown that CNTO 95 was well tolerated (6).…”
Section: Introductionmentioning
confidence: 99%